Estimation of an Examinee's Ability in the Web-Based Computerized Adaptive Testing Program IRT-CAT - Lee, Yoon-Hwan (National Health Personnel Licensing Examination Board of the Republic of Korea, 2006)
We developed a program to estimate an examinee s ability in order to provide freely available access to a web-based computerized adaptive testing (CAT) program. We used PHP and Java Script as the program languages, PostgresSQL as the database management system on an Apache web server and Linux as the operating system. A system which allows for user input and searching within inputted items and creates tests was constructed. We performed an ability estimation on each test based on a Rasch model and 2- or 3-parametric logistic models. Our system provides an algorithm for a web-based CAT, replacing previous personal computer-based ones, and makes it possible to estimate an examinee's ability immediately at the end of test.